Godność ludzka jako wartość i sposoby jej uzasadniania w opinii młodzieży - Mariański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The justification of human dignity occurs on the natural (philosophical) and supernatural (theological) or intuitive levels. The article analyzes and interprets high school and university students’ statements regarding the justifications of dignity recognised by them. The following categories of justifications were identified: a) human dignity as a guarantee and manifestation of moral life (22.4% of the total number of people surveyed); b) dignity justified by other values (15.8%); c) dignity as humanity (9.7%); d) dignity as something given and indelible (7.9%); e) dignity as a particularly important value (7.9%); f) dignity as a theological value (7.9%); g) dignity as an educational value (3.6%); h) dignity as something that is not respected (3.0%); i) dignity as a feature that distinguishes human beings from other beings (2.4%); other statements (2.4%). In the whole group of youth, 13.9% of the respondents decided not to give any answer and 3.1% gave negative answers. Most of the surveyed young people think positively about dignity, however, often in a rather shallow way, connecting it with various contents. Theological justifications come up quite rarely.